State of Domestic Violence Against Ever Married Women In Nepal (Voice of Teacher, 2021)
This study entitled “State of Domestic Violence Against Ever Married Women In Nepal” was carried out on secondary data of Nepal Demographic and Health Survey (NDHS), 2016. This study tried to identify outline of domestic violence against of ever married Women in Nepal. It has looked into the domestic violence such as physical, emotional, sexual and any kinds, of age 15-49 years of ever married women with respect to different socio-economic and demographic variables. The finding let out that physical violence increases sharply with age, from 17.7 per cent among women age 15-24 to 24.8 per cent among age 30 and above. About 36 per cent of women have experienced physical violence on other caste & ethnicity followed by Dalit (31.7%), Janajaties (20.4%) and Brahmin & Chhetri (12.2%). This study has assessed that experience of emotional violence is higher in middle class family in rural areas. Finding revealed that there is strong relation between experience of domestic violence and education level. Higher educated women were less exploited from any kinds of domestic violence in comparison to women with low level of education.